2020
DOI: 10.1093/cid/ciaa1850
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Severe Acute Respiratory Syndrome Coronavirus 2 Reinfection of a Healthcare Worker in a Belgian Nosocomial Outbreak Despite Primary Neutralizing Antibody Response

Abstract: Background It is currently unclear whether SARS-CoV-2 reinfection will remain a rare event, only occurring in individuals who fail to mount an effective immune response, or whether it will occur more frequently when humoral immunity wanes following primary infection. Methods A case of reinfection was observed in a Belgian nosocomial outbreak involving 3 patients and 2 health care workers. To distinguish reinfection from persi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 31 publications
4
33
0
1
Order By: Relevance
“…However, it was not sterizing immunity, and the virus still moderately replicated in nasal turbinates of prior infected hamsters, indicating that prior infected hamsters can be artificially re-infected after a short recovery period, even with a high level of neutralization antibodies. The conclusion is consistent with recent reports showing that recovered COVID-19 patients were re-infected in the presence of neutralizing antibodies 24,25 . A large study of a recovered cohort of 175 COVID-19 patients revealed that 6% of COVID-19 patients did not show any antibody response at all, and about 30% COVID-19 patients showed very low neutralizing antibodies 26 .…”
Section: Discussionsupporting
confidence: 93%
“…However, it was not sterizing immunity, and the virus still moderately replicated in nasal turbinates of prior infected hamsters, indicating that prior infected hamsters can be artificially re-infected after a short recovery period, even with a high level of neutralization antibodies. The conclusion is consistent with recent reports showing that recovered COVID-19 patients were re-infected in the presence of neutralizing antibodies 24,25 . A large study of a recovered cohort of 175 COVID-19 patients revealed that 6% of COVID-19 patients did not show any antibody response at all, and about 30% COVID-19 patients showed very low neutralizing antibodies 26 .…”
Section: Discussionsupporting
confidence: 93%
“…The patient described here showed mild COVID-19 symptoms in both episodes. This is in accordance with cases reported from Hong Kong [ 18 ], Belgium [ 21 ], and the Netherlands [ 19 ] but in contrast with cases from Ecuador [ 20 ] and the UK [ 11 ], where patients presented with increased symptom severity in the second infection.…”
Section: Discussionsupporting
confidence: 91%
“…Second, the virus identified in the second infection did not harbor any known spike mutation that could have enabled escape from immunity induced by the primary infection. Moreover, approximately 9 months elapsed between the two COVID-19 episodes, which is much longer than the 185 days between infections reported by Selhorst et al for a Belgian HCW [ 21 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There is one report of COVID-19 reinfection in an otherwise healthy adult 6 months after the initial infection despite production of neutralizing antibodies after the first infection. 1 This individual apparently spread COVID-19 while reinfected, likely reflecting viral replication in the nares in the absence of neutralizing antibodies at that site (ie, lack of mucosal immunity). Widespread vaccination will inevitably reduce the COVID-19 reproductive number, thereby changing the transmission dynamics in many parts of the world.…”
mentioning
confidence: 99%